2018
DOI: 10.1093/glycob/cwy087
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key amino acid residues determining ligand binding specificity, homodimerization and cellular distribution of human Galectin-10

Abstract: Charcot-Leyden crystal protein/Gal-10, abundantly expressed in eosinophils and basophils, is related to several immune diseases. Recently, crystallographic and biochemical studies showed that Gal-10 cannot bind lactose, because a glutamate residue (Glu33) from another monomer blocks the binding site. Moreover, Gal-10 actually forms a novel dimeric structure compared to other galectins. To investigate the role that Glu33 plays in inhibiting lactose binding, we mutated this residue to glutamine, aspartate, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 0 publications
1
27
0
Order By: Relevance
“…64 Subsequent studies demonstrated that CLC/Gal-10 can weakly (nonspecifically) bind to carbohydrate under several conditions, as in its monomeric state. 65,66 In addition, recent findings indicate that Gal-10 dimerizes with a novel global shape that is different from that of other prototype galectins (eg, Gal-1, Gal-2, and Gal-7) and may essentially inhibit disaccharide binding. 65,67 The lack of binding to ß-galactosides FIG 6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…64 Subsequent studies demonstrated that CLC/Gal-10 can weakly (nonspecifically) bind to carbohydrate under several conditions, as in its monomeric state. 65,66 In addition, recent findings indicate that Gal-10 dimerizes with a novel global shape that is different from that of other prototype galectins (eg, Gal-1, Gal-2, and Gal-7) and may essentially inhibit disaccharide binding. 65,67 The lack of binding to ß-galactosides FIG 6.…”
Section: Discussionmentioning
confidence: 99%
“…65,66 In addition, recent findings indicate that Gal-10 dimerizes with a novel global shape that is different from that of other prototype galectins (eg, Gal-1, Gal-2, and Gal-7) and may essentially inhibit disaccharide binding. 65,67 The lack of binding to ß-galactosides FIG 6. CLC/Gal-10-deficient (knockdown) eosinophils have fewer secondary granules, a nonproliferative phenotype, decreased MBP-1 expression, and increased secretion of EDN in response to PAF stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…However, three contradictory results showed that the weak carbohydrate binding activity may be attributed to wild type Gal-10 binding to the cross-linked agarose (or Sepharose) matrix and not to lactose [ 19 , 25 , 27 ], and the crystal structure of Gal-10 showed that it could bind mannose [ 23 ]. Recently, we generated a variant of Gal-10 (W127A) that exists as a monomer and can weakly bind to lactose-modified Sepharose [ 28 ].…”
Section: Ambiguous History Of Clc Protein/galecin-10mentioning
confidence: 99%
“…Gel filtration validated the formation of Gal-10 dimers in solution [ 25 ]. In addition, a key residue (Trp127) helps mediate Gal-10 dimerization [ 28 ]. In fact, mutation of Trp127 to alanine abolishes Gal-10 dimer formation.…”
Section: Structural Comparisons Between Gal-10 and Other Prototypementioning
confidence: 99%
See 1 more Smart Citation